Nutritional Care for Patients with Non St Elevation Myocardial Infarction (Nstemi) - Ika Wirya Wirawanti; Ludia Rami; Lydia Fanny (Jurnal Gizi dan Kesehatan Keluarga, 2024)
Background: The case study was conducted based on the Standardized Nutritional Care Process (PAGT) on a 65 year old patient, Mrs. AR. Method: The variables monitored during the study were anthropometry, biochemistry, clinical physical nutrition focus, and eating patterns for three days. Results: the study showed that the anthropometric data for a BMI of 27.5 kg/m2 was included in the obesity category, with a nutritional diagnosis of NC-3.3 and at the end of the intervention the patient's nutritional status was still obese. The patient's laboratory examination, RGB, HGB, and HCT decreased by 3.2 mg/dl, 8.8 mg/dl and 28 mg/dl and hemoglobin decreased by 8.8 gr/dl, with a nutritional diagnosis of NI-5.1 and until the end intervention, RGB, HGB, and HCT levels still decreased. The dietary interventions given were the heart diet and the DASH diet with the consistency of chopped rice. Based on the results of the 24 hour recall, the patient's food intake was in the deficient category, namely 43.9% energy, 37.6% protein, 54.7% fat, 42.6% carbohydrates with a nutritional diagnosis of NI -2.1 and until the end of the patient's intake intervention continue to increase. Conclution: that there was an improvement in the patient's condition after being given intervention, especially regarding the patient's diet/intake.